2001
DOI: 10.1080/00480169.2001.36212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a peri-parturient eprinomectin treatment of dairy cows on milk production

Abstract: These data provide evidence that the use of a peri-parturient treatment of eprinomectin on multiparous cows can increase their production of fluid milk and milksolids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Although higher treatment responses in older cattle may appear counterintuitive, as these animals are considered to be functionally immune to gastrointestinal nematodes, several previous studies reported higher treatment responses with increasing cow age [3,13,25]. As discussed before [3], the latter may be attributed to a different priority of nutrient allocation between primi-and multiparous cows [13] or the higher energy requirements of the immune response to GI nematodes in older animals, as observed in sheep [32]. Finally, it may also be considered that the level of GI nematode infection in primiparous cows is generally lower than in older cows.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although higher treatment responses in older cattle may appear counterintuitive, as these animals are considered to be functionally immune to gastrointestinal nematodes, several previous studies reported higher treatment responses with increasing cow age [3,13,25]. As discussed before [3], the latter may be attributed to a different priority of nutrient allocation between primi-and multiparous cows [13] or the higher energy requirements of the immune response to GI nematodes in older animals, as observed in sheep [32]. Finally, it may also be considered that the level of GI nematode infection in primiparous cows is generally lower than in older cows.…”
Section: Discussionmentioning
confidence: 99%
“…The parameter yielding most consistent results is the anti-Ostertagia ostertagi antibody level in individual milk samples, with studies showing higher treatment responses in cows with a high antibody level [3,11,12,16]. As for the age of the cow, some studies found no relationship with treatment effect [10,14,17], whereas others reported a higher milk yield gain in older cows [3,13] or conversely, in younger cows [5]. Finally, it was suggested that treatment responses were higher in high producing animals [14,18], but this was not observed by others [10].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The cattle were naturally infested with C. bovis, as confirmed by examination of skin scrapings taken the day before treatment (day −1). To exclude effects on production resulting from the anthelmintic properties of eprinomectin (Little et al 2000;Zaffaroni et al 2000;McPherson et al 2001;Nødtvedt et al 2002), all animals were dewormed with oral fenbendazole (Panacur Suspension 10%, Hoechst Roussel Vet, Germany) administered at twice the manufacturer's recommended dose on day −6.…”
Section: Methodsmentioning
confidence: 99%
“…No other MLs are approved for treatment of dairy animals. There is concern that unapproved ML products may be used in dairy animals, especially when there are claims that use of the approved (and more expensive) drug eprinomectin can increase milk yield [86,87]. Concerns over the presence of ML residues in milk are supported by the fact that as much as 5% of the drug dosage may be excreted in milk after treatment with certain unapproved ML products [33,37,72].…”
Section: Monitoring For Macrocyclic Lactone Residues In Foodmentioning
confidence: 97%